Freud and his critics - Robinson, Paul A., 1940- (Berkeley : University of California Press, 1993)
"With admirable clarity, Paul Robinson painstakingly reconstructs and then relentlessly dismantles the arguments of Freud's most tenacious and recent debunkers. The results stunningly vindicate the abiding power of psychoanalysis as a master discourse of our age."--Martin Jay, Professor of History, University of California, Berkeley.
Introduction: The anti-Freudian mood -- Freud as closet sociobiologist / Frank Sulloway -- Freud, seduction, and the new Puritanism / Jeffrey Masson -- The philosophical critique of Freud / Adolf Grünbaum -- Conclusion : Freud and intellectual history.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Freud, Sigmund, -- 1856-1939.; Sulloway, Frank J. -- Views on psychoanalysis; Masson, J. Moussaieff -- 1941- -- Views on psychoanalysis; Grünbaum, Adolf -- Views on psychoanalysis; Freud, Sigmund, -- 1856-1939; Sulloway, Frank J; Masson, J. Moussaieff -- 1941-; Grünbaum, Adolf; Freud, Sigmund, -- 1856-1939.; Sulloway, Frank J. -- Et la psychanalyse; Masson, Jeffrey Moussaieff, -- 1941- -- Et la psychanalyse; Grünbaum, Adolf -- Et la psychanalyse; Freud, Sigmund, -- 1856-1939; Grünbaum, Adolf; Masson, J. Moussaieff -- 1941-; Sulloway, Frank J; Sulloway, Frank J. -- 1947-; Freud, Sigmund -- 1856-1939; Masson, Jeffrey Moussaieff -- 1941-; Grünbaum, Adolf -- 1923-2018; Freud, Sigmund, -- 1856-1939.; Sulloway, Frank J; Masson, J. Moussaieff -- 1941-; Grünbaum, Adolf; Freud, Sigmund, -- 1856-1939 -- Critique et interprétation.; Freud, Sigmund; Psychoanalysis -- Philosophy -- History; Freudian Theory -- history; Psychanalyse -- Philosophie -- Histoire; PSYCHOLOGY -- Reference; Psychoanalysis; Psychoanalysis -- Philosophy; Aufsatzsammlung; Psychoanalyse; Psychoanalyse; Psychoanalysis -- Philosophy -- History; Psychanalyse -- Philosophie -- Histoire; Psychoanalysis; History